Hydrogen bonding: a mechanism for tuning electronic and optical properties of hybrid organic–inorganic frameworks - Fedwa El-Mellouhi (2011099) (2016)
The field of hybrid inorganic–organic framework materials is one of the fastest growing fields in materials science because their enormous structural and chemical diversity presents great opportunities for creating many technologically relevant properties. One of the most important issues is controlling and tuning the structural, optical, thermal, mechanical and electronic properties of these complex materials by varying their chemistry, fabrication techniques and preparation conditions. Here we demonstrate that significant progress in this area may be achieved by introducing structural elements that form hydrogen bonds with the environment. Considering hybrid framework materials with different structural ordering containing protonated sulfonium cation H3S+ and electronegative halogen anions (I−, Br−, Cl− and F−), we found that hydrogen bonding increases the structural stability of the material and may be used for tuning electronic states near the bandgap. We suggest that such a behaviour has a universal character and should be observed in hybrid inorganic–organic framework materials containing protonated cations. This effect may serve as a viable route for optoelectronic and photovoltaic applications. Other Information Published in: npj Computational Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/npjcompumats.2016.35